Study of perforated plates stretching by finite element method - Куценко, О. Г.; Куценко, А. Г.; Харитонова, Л. В. (Київський національний університет імені Тараса Шевченка, 2021)
The problem of axial stretching of a plate with a double-periodic system of round holes arranged in a checkerboard pattern is considered. The specified problem is reduced to elasticity second problem for one period of plate, which was solved by the finite element method. As a result, the reduced elastic characteristics of the equivalent homogeneous orthotropic plate are found. The analysis of their behavior depending on dimensionless geometrical parameters is carried out. The area of variation of the geometric parameters was divided into two subareas. The behavior of the equivalent elastic characteristics in these areas is significantly different. It turned out that the double-periodic perforated plate shows significantly anisotropic behavior. The limit values of the Poisson's ratios can reach unity and, on the other hand, may be less than the original value. Dependences of the stress concentration coefficient on dimensionless geometrical parameters are obtained too. Performed comparative analysis of the obtained results with the results known from the literature, confirmed their adequacy. Pages of the article in the issue: 55 - 58 Language of the article: Ukrainian
Keywords: double-periodic; perforated plate; tension; двояко-періодична; перфорована пластинка; розтяг